Religious Moderation as a New Approach to Learning Islamic Religious Education in Schools - Husna, Ulfatul; Thohir, Muhammad (FITK UIN Walisongo, 2020)
Islam as a religion with a slogan that brings grace to the universe, however historically not all religious articulations are compatible. One example is extreme attitudes in religion. The most important element in realizing the peace mission in schools is learning Islamic Religious Education (PAI). This study was conducted to reveal how to maintain religious moderation in schools in preventing extremism. This field study at SMA Negeri 1 (Senior High School) Krembung, East Java, Indonesia uses a qualitative descriptive method. The results showed that school moderation uses three main principles, namely tawassuth, ta'adul and tawazun. These principles are able to create a moderate situation, create a school of peace, progress, and form a generation with moderate views.Â Abstrak Islam sebagai agama dengan semboyan pembawa rahmat bagi alam semesta, namun secara historis tidak semua artikulasi agama itu cocok. Salah satu contohnya adalah sikap ekstrim dalam beragama. Elemen terpenting dalam mewujudkan misi perdamaian tersebut di sekolah adalah pembelajaran Pendidikan Agama Islam (PAI). Studi ini dilakukan untuk mengungkap bagaimana mempertahankan moderasi beragama di sekolah dalam mencegah ekstrimisme. Studi lapangan di SMA Negeri 1 Krembung, Jawa Timur, Indonesia ini menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa moderasi beragama sekolah menggunakan tiga prinsip utama yaitu tawassuth, taâ€™adul dan tawazun. Prinsip-prinsip ini mampu menciptakan situasi yang moderat danÂ mewujudkan sekolah damai, berkemajuan dan membentuk generasi yang berpandangan moderat.